Effect of the CHS on Seismic Responses of the Single-Layer Spherical Reticulated Shell under Vertical Seismic Motions - Jie Xu; Renjie Liu; Ce Ji; Chao Wang; Guangyong Wang (Advances in Civil Engineering)
Single-layer spherical reticulated shells are typical roof structures for the gymnasiums. The center-hung scoreboard (CHS) is large weight display device which is usually suspended on the roof of the gymnasium. The effect of the CHS on the dynamic characteristics and seismic responses of the single-layer spherical reticulated shell (SPRS) is not fully clear. In this paper, the effect of the CHS on the SPRS under vertical seismic action is investigated. Two kinds of FE models are built with Abaqus software, including the flexibly suspended model and the simplified model. In a simplified model, the CHS is simplified as four fixed masses on the four CHS suspension nodes. The dynamic explicit method is used for the seismic responses, and the Lanczos method is used for the dynamic characteristics. The influence of the CHS weight and the sling length of on dynamic characteristics and seismic responses are analysed. It turns out that in the flexibly suspended model, the first three vibration modes are free swing of the CHS, and the CHS weight and the sling length have a significant impact on the fourth and subsequent modes. The length of the sling has a large impact on some low-order frequencies, but has little impact on the high-order frequencies. Compared with the simplified model, the axial forces of some structural members and some nodal acceleration in the flexibly suspended model under vertical seismic motions would increase by as high as 523% and 564%, respectively. It turns out that the seismic responses of the SPRS would be underestimated if a simplified model is used for analysis. The region in the central of the SPRS, the hoop members of the SPRS, and the support platform are the most affected regions in terms of both axial force and nodal acceleration.